The effectiveness of gamification to enhance students’ mastery on tenses viewed from students’ creativity - Benny Krisbiantoro (Journal of Advanced Multidisciplinary Research, 2020)
The advancement of ICT has resulted in the fast development of games industry by which teachers are creative to design the learning process and to utilize various kinds of gamifications. Gamification is a teaching method that uses game elements with the aim of motivating students to be directly involved in games and learning at the same time so that students get an interesting and enjoyable learning experience. Although many studies have been conducted related to the use gamification, the study on the use of gamification to improve tenses mastery regarded the students’ creativity is rarely found. This study was aimed to investigate whether: (1) gamification was more effective than conventional teaching method in enhancing tenses mastery of the second semester students of nursing diploma III; (2) the second semester students with high level of creativity had better tenses mastery than those with low level of creativity; and (3) there was an interaction effect between teaching methods and creativity on enhancing tenses mastery of the second semester students of nursing diploma III of faculty of health of Universitas Harapan Bangsa. The method which was employed in this research was an experimental research. The population of the research was the second semester students of nursing diploma III of faculty of health of Universitas Harapan Bangsa. Two classes were taken by using total sampling technique. The samples in this research were two classes; experimental class consisting of 30 students from 2A-1 and control class consisting of 30 students from 2A-2. The research instruments consisted of verbal creativity and tenses mastery test. The data were obtained from creativity and tenses mastery test. They were analysed in the terms of their frequency distribution, normality of the sample distribution, and the data homogeneity and then ANOVA test (Multifactor Analysis and Variance) and TUKEY test to test the research hypotheses. The result of the research findings leads to the conclusion that: (1) gamification is more effective than conventional teaching method to enhance tenses mastery of the second semester students; (2) the students having high creativity have better tenses mastery than those having low creativity; and (3) there is an interaction between teaching methods and creativity on enhancing tenses mastery.